Substitution methods, mean plugging in the other formula.
Let see
1. y+x=7
2. y+3=x
So for number 2 you can do --> subtract 3 to the other side and it will equal y=x-3
Then you plug the new equation to equation number one, when you see y so it would be (x-3)+x=7
andd...2x-3=7
add 3 to both side, and it would be 2x=10
divde by 2, x = 5
now to find the y value
plus the value for x for the first equation >>y+(5)=7
subtract 5 at both side
y=2
now we check
1. 5+2=7 check!
2. 2+3=5 check!!
Correctt.. LOl
2007-01-07 17:26:26
·
answer #1
·
answered by Azumi 2
·
1⤊
0⤋
y + x = 7- - - - - Equatiion 1
y + 3 = x- - - - - Equation 2
- - - - - - -
Substitute method equation 2
y + 3 = x
y + 3 - 3 = x - 3
y = x - 3
The answer is y = x - 3
Insert they value into equation 1
- - - - - - - - - - - - - - - - - - - - -
y + x = 7
x - 3 + x = 7
2x - 3 = 7
2x - 3 + 3 = 7 + 3
2x = 10
2x/2 = 10/2
x = 5
The answer is x = 5
Insert the x vallue into equation 1
- - - - - - - - - - - - - - - - - - - - - -
y + x = 7
y + 5 = 7
y + 5 - 5 = 7 - 5
y = 2
The anser is y = 2
Insert the y value into equation 1
- - - - - - - - - - - - - - - - - - - - - -
Check for equation 1
y + x = 7
2 + 5 = 7
7 = 7
- - - - - - - -
Check for euation 2
y + 3 = x
2 + 3 = 5
5 = 5
- - - - - - - - -
The solution set is { 5, 2 }
- - - - - -s-
2007-01-08 11:52:56
·
answer #2
·
answered by SAMUEL D 7
·
1⤊
0⤋
Take the second equation and substitute it into the first equation:
y+y+3=7
2y+3=7
2y=4
y=2
2+3=x
x=5
The solution set is (5,2)
Check:
2+5=7
7=7
2+3=5
5=5
2007-01-08 09:40:47
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
y+x=7
y+3=x substitute this for x in the equation above
y+(y+3)=7
2y+3=7
2y=4
y=2 substitute this in the 2nd equation
y+3=x
2+3=x
x=5
(5, 2)
2007-01-08 01:27:49
·
answer #4
·
answered by yupchagee 7
·
1⤊
0⤋
In the substitution method, you substitute one thing for another. Since we know that x = y + 3, let's substitute that into the other equation.
y + (y + 3) = 7
2y + 3 = 7
2y = 4
y = 2
So x = 5. You can check by putting those values for x and y into both equations.
2007-01-08 01:21:13
·
answer #5
·
answered by ? 6
·
1⤊
0⤋
to do substitution mean put the value of the variable that has been given into the first equation.
y+x=7....(i)
x=y+3.....(ii)
put the (ii) into (i) as the value of x.
y+y+3=7
2y+3=7
2y=7-3
2y=4
2y/2=4/2
y=2
to find x put 2 where ever you see y in the (i) equation.
y+x=7 ...(i)
2+x=7
x=7-2
x=5.
remember that you can substitute the value of y into any of the two equation,but when you have a negative sign in one try to avoid that
good luck.
2007-01-08 02:26:38
·
answer #6
·
answered by bright 247 2
·
1⤊
0⤋
y+x=7
y+3=x
x + y =7(1)
x - y =3(2)
x + y =7
2x = 10 ( (1) + (2) )
x = 5
y = 2
2007-01-08 01:26:10
·
answer #7
·
answered by James Chan 4
·
1⤊
0⤋
y+x = 7 ---- (i)
y+3 = x ---- (ii)
from equation (ii), substitute the value of x in equation (i)
=> y+(y+3) = 7
=> 2y+3 = 7
=> 2y = 4
=> y = 2
now, substitute this value of y in equation (ii)
=> 2+3 = x
=> 5 = x
2007-01-08 01:26:38
·
answer #8
·
answered by rishi 2
·
1⤊
0⤋